Preservice teachers’ adaptations to tensions associated with the edTPA during its early implementation in New York and Washington states - Meuwissen, Kevin W.; Choppin, Jeffrey M. (Education Policy Analysis Archives, 2015)
The edTPA is a teaching performance assessment (TPA) that the states of New York and Washington implemented as a licensure requirement in 2013. While TPAs are not new modes of assessment, New York and Washington are the first states to use the edTPA specifically as a compulsory, high-stakes policy lever in an effort to strengthen the quality and accountability of teachers and teacher educators. This study examines 24 New York and Washington teaching candidates’ experiences with the edTPA during its first year of consequential use for state certification. The data, drawn from qualitative interviews that were part of a larger mixed-methods study, reveal that preservice teachers had to mediate several tensions associated with the edTPA’s dual role as a formative assessment tool and a licensure mechanism. In this paper, we identify those tensions, describe candidates’ efforts to mediate them, and discuss the extent to which that mediation process may or may not contribute to the improvement of teachers’ practices. Given the edTPA’s positioning in a policy context – specifically, the potential for the assessment’s locus of control, high stakes, and opaque rating process to distort the procedures it is intended to measure – the paper concludes with recommendations for teacher education programs aimed at capitalizing on the edTPA’s benefits and mitigating its unproductive tensions.